2012
DOI: 10.1038/modpathol.2011.171
|View full text |Cite
|
Sign up to set email alerts
|

MYC gene amplification is often acquired in lethal distant breast cancer metastases of unamplified primary tumors

Abstract: In breast cancer, amplification of MYC is consistently observed in aggressive forms of disease and correlates with poor prognosis and distant metastases. However, to date, a systematic analysis of MYC amplification in metastatic breast cancers has not been reported. Specifically, whether the MYC amplification status may change in metastases in comparison to the corresponding primary breast tumor, and potential variability among different metastases within the same patient have also not been assessed. We genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 33 publications
7
54
1
Order By: Relevance
“…However, our study demonstrated that, despite MYC expression spanning accross all the intrinsic subtypes of breast cancer determined in our primary and metastatic samples, there was a tendency toward a higher MYC positivity rate in the luminal subtype, as compared to the other subtypes, although this tendency was not statistically significant (P=0.13). This result contradicts those of other studies demonstrating a clear association between MYC amplification and ER-negative or basal breast cancers (9,(29)(30)(31). It is possible that, in luminal A tumors displaying low Ki67 scores, MYC expression reflects biological characteristics of the tumor cell population other than its proliferative state.…”
Section: Clinicoc-myc (Cyt) C-myc (Nuc) Ki67 P-mtor P-akt Pathologicacontrasting
confidence: 89%
See 2 more Smart Citations
“…However, our study demonstrated that, despite MYC expression spanning accross all the intrinsic subtypes of breast cancer determined in our primary and metastatic samples, there was a tendency toward a higher MYC positivity rate in the luminal subtype, as compared to the other subtypes, although this tendency was not statistically significant (P=0.13). This result contradicts those of other studies demonstrating a clear association between MYC amplification and ER-negative or basal breast cancers (9,(29)(30)(31). It is possible that, in luminal A tumors displaying low Ki67 scores, MYC expression reflects biological characteristics of the tumor cell population other than its proliferative state.…”
Section: Clinicoc-myc (Cyt) C-myc (Nuc) Ki67 P-mtor P-akt Pathologicacontrasting
confidence: 89%
“…protein overexpression in the epithelial component of breast cancer (6)(7)(8)(9)(22)(23)(24). However, we were unable to identify any correlation between MYC expression and axillary lymph node positivity in our series, confirming the results of previous studies (5,6,25).…”
Section: Clinicoc-myc (Cyt) C-myc (Nuc) Ki67 P-mtor P-akt Pathologicasupporting
confidence: 89%
See 1 more Smart Citation
“…[44][45][46][47][48][49][50][51][52][53][54][55] Both OSM/STAT3-and TGFb-induced senescence require the repression of MYC. 40,[56][57][58][59] Our lab has previously demonstrated that the expression of MYC from a constitutive promoter prevents OSM-or RAS-induced senescence and alters the response of HMEC to persistent oncogenic stimuli, from growth suppressive to growth promoting.…”
Section: Persistent Osm/stat3 Signaling Promotes Smad Targetgene Tranmentioning
confidence: 99%
“…This manner of MYC induction is fairly common in cancer, affects all MYC family members, and can take the form of small focal amplifications [126,127], large amplifications [128], and doubleminute chromosomes [129]. Although increasing the number of copies of MYC does not always correlate with MYC overexpression [130,131], the frequency with which MYC gene amplification occurs and the correlation of this event with metastatic disease and poor prognosis [132] strongly indicate a direct role for MYC gene amplification in many human malignancies.…”
Section: Myc Deregulation In Cancermentioning
confidence: 99%